2020
DOI: 10.3390/s20205825
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Filterless, Multi-Point, and Temperature-Independent Fiber Bragg Grating Dynamical Demodulator Using Pulse-Width Modulation

Abstract: We demonstrated in this work a filterless, multi-point and temperature-independent FBG (fiber Bragg grating) dynamical demodulator using pulse-width-modulation (PWM). In this approach, the FBG interrogation system is composed of a tunable laser and a demodulator that is designed to detect the wavelength shift of the FBG sensor without any optical filter making it very suitable to be used in harsh environments. In this work, we applied the proposed method that uses the PWM technique for FBG sensors placed in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In [11], J.B. Rosolem et al, demonstrated a filterless, multipoint, and temperatureindependent FBG dynamical demodulator using pulse-width modulation (PWM). In this approach, the FBG interrogation system was composed of a tunable laser and a demodulator that was designed to detect the wavelength shift of the FBG sensor without any optical filter, making it very suitable for use in harsh environments.…”
Section: Original Interrogatorsmentioning
confidence: 99%
“…In [11], J.B. Rosolem et al, demonstrated a filterless, multipoint, and temperatureindependent FBG dynamical demodulator using pulse-width modulation (PWM). In this approach, the FBG interrogation system was composed of a tunable laser and a demodulator that was designed to detect the wavelength shift of the FBG sensor without any optical filter, making it very suitable for use in harsh environments.…”
Section: Original Interrogatorsmentioning
confidence: 99%